Edukasi Kesiapsiagaan Bencana Gempa Bumi dan Tsunami di SD Negeri Krajan - Rismayanti, Rismayanti; Fatimah, Fatma Siti; Sarwadhamana, Raden Jaka; Dami, Nur Anisa; Muhajir, Mia Aulia; Prasetyaningrum, Lia; Oktasania, Nafaati; Saputri, Maulida Ayu (Universitas Muhammadiyah Magelang, 2023)
Abstract Background : Preparedness is a series of activities carried out to anticipate disasters through organization and through appropriate and effective steps. In the face of disaster, preparedness is the key to safety. This shows that an earthquake disaster preparedness plan is needed so that it can minimize the losses that will occur. The provision of Earthquake and Tsunami Disaster Preparedness education was carried out on December 01, 2023 at Krajan Poncosari Srandakan Bantul State Elementary School. The number of students is 31 people consisting of 18 male students and 13 female students. Krajan State Elementary School Poncosari Srandakan Bantul is located in the lowlands 2 KM away from the coast. This causes Krajan State Elementary School to often feel earthquakes and also the risk of tsunamis, because the location of Krajan State Elementary School is located between one of the tectonic plates, namely the Indian Ocean. Aim : With the provision of earthquake and tsunami disaster preparedness education provided by Alma Ata University students, it can provide benefits and refresh the knowledge of children of SD Negeri Krajan Poncosari Srandakan Bantul in facing earthquake and tsunami disasters. Methods : The design used in this study was pre-experiment with one-group pre-post test design. This study does not have a comparison group or control group but the first observation (pre test) is carried out so that researchers can test changes that occur after treatment. This research is a type of